The Shallow Ecology Perspective on The Little Prince Novel By Antoine De Saint-Exupéry - Mutmainnah; Nurlailatul Qadriani (ELITE: Journal of English Language and Literature, 2025)
The narration about the bond between humans and nature in literary works is an element that is quite easy to find, but unfortunately this narrative does not seem to mean anything other than to evoke and dissolve the reader in the form of familiarize.  The ecological perspective in Antoine de Saint-Exupéry's novel "The Little Prince", which tells the journey of a young prince across different planets, emphasizes the complicated relationship between humans and the environment. Between care, responsibility, and interconnectedness between all beings. The findings reveal that "The Little Prince" advocates environmental awareness that challenges materialistic attitudes and is often negligent in adulthood. By depicting the childlike wonder of the prince and the deep emotional connection with nature, the text encourages readers to adopt a more empathetic and holistic view of their environment. This perspective is particularly relevant in contemporary discussions about ecological sustainability and the moral obligation that humans have towards the planet. Through qualitative descriptive analysis, this research highlights the importance of fostering a sense of concern and appreciation for the environment, as articulated in the prince's reflection. Ultimately, the study states that "The Little Prince" serves as a reminder of the need for humans to connect with nature, advocating for a shift in perception that aligns with ecological principles and promotes a more sustainable future. Using a shallow ecology approach, this exploration not only enriches the literary interpretation of the text, but also contributes to the ongoing dialogue about human ethics and responsibility towards the environment.